Using PeptideAtlas, SRMAtlas, and PASSEL: Comprehensive Resources for Discovery and Targeted Proteomics. Issue 1 (17th June 2014) - Kusebauch, Ulrike; Deutsch, Eric W.; Campbell, David S.; Sun, Zhi; Farrah, Terry; Moritz, Robert L.
Abstract: PeptideAtlas, SRMAtlas, and PASSEL are Web‐accessible resources to support discovery and targeted proteomics research. PeptideAtlas is a multi‐species compendium of shotgun proteomic data provided by the scientific community; SRMAtlas is a resource of high‐quality, complete proteome SRM assays generated in a consistent manner for the targeted identification and quantification of proteins; and PASSEL is a repository that compiles and represents selected reaction monitoring data, all in an easy‐to‐use interface. The databases are generated from native mass spectrometry data files that are analyzed in a standardized manner including statistical validation of the results. Each resource offers search functionalities and can be queried by user‐defined constraints; the query results are provided in tables or are graphically displayed. PeptideAtlas, SRMAtlas, and PASSEL are publicly available freely via the Web site http://www.peptideatlas.org . In this protocol, we describe the use of these resources, we highlight how to submit, search, collate and download data. Curr. Protoc. Bioinform . 46:13.25.1‐13.25.28. © 2014 by John Wiley & Sons, Inc.